Glyco-genes change expression in cancer through aberrant methylation - Vojta, Aleksandar; Samaržija, Ivana; Bočkor, Luka; Zoldoš, Vlatka (Biochimica et biophysica acta, 2016)
Most eukaryotic proteins are modified by covalent addition of glycan molecules that considerably influence their function. Aberrant glycosylation is profoundly involved in malignant transformation, tumor progression and metastasis. Some glycan structures are tumor-specific and reflect disturbed glycan biosynthesis pathways. We analyzed DNA methylation and expression of 86 glyco-genes in melanoma, hepatocellular, breast and cervical cancers using data from publicly available databases. We also analyzed methylation datasets without the available matching expression data for glyco-genes in lung cancer, and progression of melanoma into lymph node and brain metastases. Ten glyco-genes (GALNT3, GALNT6, GALNT7, GALNT14, MGAT3, MAN1A1, MAN1C1, ST3GAL2, ST6GAL1, ST8SIA3) showing changes in both methylation and expression in the same type of cancer belong to GalNAc transferases, GlcNAc transferases, mannosidases and sialyltransferases, which is in line with changes in glycan structures already reported in the same type of tumors. Some of those genes were additionally identified as potentially valuable for disease prognosis. The MGAT5B gene, so far identified as specifically expressed in brain, emerged as a novel candidate gene that is epigenetically dysregulated in different cancers other than brain cancer. We also report for the first time aberrant expression of the GALNT and MAN genes in cancer by aberrant promoter methylation. Aberrant expression of glyco-genes due to aberrant promoter methylation could be a way leading to characteristic glycosylation profiles commonly described in cancer. Methylation status in promoters of candidate glyco-genes might serve as prognostic markers for specific tumors and point to potential novel targets for epigenetic drugs. This article is part of a Special Issue entitled "Glycans in personalised medicine" Guest Editor: Professor Gordan Lauc. •Identification of glyco-genes showing changed expression and methylation in different types of cancer•A subset of ten glyco-genes consistently shows both aberrant expression and CpG methylation•Some of the identified genes show potential as prognostic markers in certain types of cancer.